2018
DOI: 10.1590/1414-431x20177090
|View full text |Cite
|
Sign up to set email alerts
|

Lipid core nanoparticles resembling low-density lipoprotein and regression of atherosclerotic lesions: effects of particle size

Abstract: Particles are usually polydispersed and size is an important feature for lipid-based drug delivery systems in order to optimize cell-particle interactions as to pharmacologic action and toxicity. Lipid nanoparticles (LDE) with composition similar to that of low-density lipoprotein carrying paclitaxel were shown to markedly reduce atherosclerosis lesions induced in rabbits by cholesterol feeding. The aim of this study was to test whether two LDE fractions, one with small (20–60 nm) and the other with large (60–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…As underlined in the introduction, the potentialities of lipid core nanoparticles such as nanostructured lipid carriers to target atherosclerotic lesions have remained largely unexplored, despite few promising results [24,25,26,27,28]. However, NLC display suitable features in terms of particle size, composition, in vivo tolerance, and potential translation to the clinic (easily up-scaled production at a very reasonable cost) for nanomedicine application in the cardiovascular field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As underlined in the introduction, the potentialities of lipid core nanoparticles such as nanostructured lipid carriers to target atherosclerotic lesions have remained largely unexplored, despite few promising results [24,25,26,27,28]. However, NLC display suitable features in terms of particle size, composition, in vivo tolerance, and potential translation to the clinic (easily up-scaled production at a very reasonable cost) for nanomedicine application in the cardiovascular field.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid nanoparticles prepared by nanoprecipitation/solvent diffusion method and loaded with lovastatin were shown to accumulate in macrophages and foam cells present in atherosclerotic plaques [24]. Maranhão’s group developed paclitaxel-oleate [25] and carmustine [26] loaded lipid nanoparticles produced by a microfluidization process, and showed that their intravenous administration could reduce atherosclerosis lesions in rabbits. Slightly different nanoparticles, based on a perfluorocarbon oily core, were developed in Wickline’s group for MRI atherosclerosis imaging [27] but also for therapeutic purposes [28].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, cholesteryl-core based LMPs loaded with paclitaxel, were injected into rabbits fed a high cholesterol diet. These LMPs showed significant atheroprotection, demonstrated by a reduction in intima, lesion extension and number of macrophages in the intima [ 246 ]. Carmustine has also been loaded into cholesteryl-core LMPs and reduced the lesion size by 90% and inhibited the accumulation of macrophages, T cells and vascular SMCs at the intima in a rabbit model [ 247 ].…”
Section: Advancements In Strategies For Delivering Lipoproteinsmentioning
confidence: 99%
“…Macrophage phagocytic activity and lipoprotein metabolism are potentially implicated biological pathways to investigate. 41 NLC present strong structural similarity with chylomicrons in terms of lipid composition, and with VLDL in terms of particle size. Since Q4 now, other lipoprotein classes, LDL and HDL, have attracted attention for the design of imaging and drug delivery Figure 6.…”
mentioning
confidence: 94%
“…Solid lipid nanoparticles loaded with iron oxide particles and PG12 prostacyclin, and stabilized with nucleolipids, were demonstrated to reduce in vitro platelet aggregation. 50 Lipid nanoparticles prepared by microfluidization and loaded with paclitaxel-oleate 41 or carmustine 51 were shown to reduce atherosclerosis lesions in rabbits. Wickline's group has also explored the potential of slightly different nanoparticles, based on a perfluorocarbon oily core, for MR atherosclerosis imaging 52 but also for therapeutic purposes.…”
mentioning
confidence: 99%